Zonasi Kawasan Wisata Pantai di Kota Padang Sumatera Barat Menggunakan Pemodelan Viewshed - Putri, Shalsabila Lachenda; Syarief, Azhari (Lembaga Yasin AlSys, 2024)
Padang City is one of the cities in West Sumatra which has a coastline with a coastline of 68 km. The coast of Padang City is a special interest tourist area in West Sumatra Province. This research aims to determine the approximate zoning of coastal tourist areas using geotagging photo data and determine the range of visibility using viewshed modeling. Zoning is carried out using the Kernel Density method. Kernel Density divides zones through the density of geotagging photo coordinate point data. In this research, the geotagging photo data used is photos that capture coastal views in the city of Padang. The viewshed is carried out towards the mainland because it has topographic diversity. This type of research is qualitative research. The data used is secondary data obtained through the Ina-Geoportal agency. The results of the research showed that there are 6 core zones of coastal tourist areas that are usually visited by tourists in Padang City, West Sumatra Province. The tourist beach area has a viewshed area ranging from 0.174 km2 to 4,569 km2.